Microbial Diversity in Rainwater with Correspondence to Particulate Matter and Environmental Factors - Perera, Walgampolage Achintha Kalani; Magana-Arachchi, Dhammika Nayoma (Journal of Sustainability and Environmental Management, 2022)
Microbial composition in rainwater has emerged as a trending research topic due to the increased use of rainwater harvesting systems (RWHS) worldwide. Studies have been conducted to analyze potentially pathogenic microorganisms in RWHS. However, the core focus in most papers has been on the rainwater collected in the storage tanks rather than the composition of microorganisms in fresh rainwater. Due to the microbial influence on air quality, this review dissects various studies that have identified the types of microorganisms in rainwater and their correspondence with atmospheric microbiota to understand airborne microbial movement and its effect. Current methods for rainwater analysis and technologies such as air mass models, that map the distribution of airborne microorganisms throughout the atmosphere, were evaluated to define factors that allow these organisms to move through different levels of the atmosphere. Additionally, the correlation between organisms found in rainwater and particulate matter was analyzed. This review discusses the importance of analyzing rainwater directly without limiting it to RWHS, like roof-harvested rainwater, in microbial source tracking. The paper also presents an overview of ecological contributions by microorganisms at a tropospheric level. Research gaps were noted in identification techniques, the type of microorganisms studied, and their ecological purposes, including paucity in viral detection. The uniqueness of this review is that potential new techniques were explored for prospective studies to improve and further analyze the microbial communities in rainwater. The more focus we give to microbial communities in fresh rainwater in the future, the easier it will be to predict the levels of pathogenicity and disease transmission related to airborne microbiota.